Geraldine Barnes: Bookish riddarasögur. Writing Romance in Me-dieval Iceland. The Viking Collection 21. - Divjak, Alenka (Collegium Medievale, 2016)
Today it is generally accepted by the scholarship that the Icelandic riddarasögur, a cor-pus of ca. 30 Icelandic derivatives of medieval romance, supposedly written in the fourteenth and fifteenth centuries, are indebted to the translated riddarasögur in terms of their subject matter, style and ethos. However, apart from the motifs borrowed from the translated riddarasögur, such as feasts, tournaments, travels, bridal quests, fights, adventures in distant lands etc., several Icelandic riddarasögur derive a consid-erable portion of their narrative material from encyclopaedic and historiographical traditions, accessible to medieval Icelanders in various Old Norse translations and adaptations: encyclopaedias, the life of Alexander the Great, Sallust and Lucan’s his-tories of the Roman fights in North Africa, the history of Troy, the history of the Jews, the adaptation of Historia Regum Britanniae etc. It is the function of all this en-cyclopaedic, geographical and historiographical material in the Icelandic riddarasögur as well the sagas’ interaction with the world of books and learning which is the central topic in the monograph Bookish riddarasögur by Professor Emeritus Geraldine Barnes, who in her book focuses on ca. 15 Icelandic riddarasögur marked by a distinctive book-ish and learned background. Professor Emeritus Barnes is noted for an extensive bib-liography in the field of learned traditions in translated and Icelandic riddarasögur: Tristrams saga ok Ísöndar and Arthurian legend, medieval geography, giants, travels to exotic lands, a concept of monstrosity, the abuse of learning, Byzantium in rid-darasögur, the legend of Prester John, and now she presents her work in this still rather unexplored field in an expanded and systematic book form.